THE CORELLATION BETWEEN AGE AND PARITY TO THE INCIDENCE OF PREECLAMPSIA OR ECLAMPSIA IN LABOUR - Fatimah Fatimah; Nurulita Nurulita; Arniah Arniah (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: Based on Indonesian Health Demographic Survey 2007 maternal mortality rates are 228 per 100.000 live births. In East Kalimantan, maternal mortality was recorded at 90 cases, one of death caused by pre-eclampsia/eclampsia. In 2011, from 923 women in labor in Panglima Sebaya General Hospital there are 307 had pre-eclampsia/eclampsia. Pre-eclampsia or eclampsia be influenced by several risk factors such as primigravidae and ages. Aims: The purpose of this study is to know the correlation of age and parity with pre-eclampsia/eclampsia on women in labor, in Panglima Sebaya, General Hospital. Methods: This study used cross sectional design. Sampling methods used purposive sampling, the number of samples is 340 cases. Data analysis using SPSS for Windows Release 16.0 programmes. Bivariate analysis used chi-square test and multivariate analysis used regress logistic test. Result: chi-square test for primigravidae has p-value(0.002) < 0,05 and Ratio Prevalence (RP) = 1.988 (95% CI 1.296 – 3.079). variabel of ages p-value(0,000) < 0.05 RP = 2.661 (95% CI 1.656 – 4.116). and for regress logistic test for variable of primigravidae the result is p-value(0,003) < 0.05 and coefficients regress 0.665, variable of ages has p-value(0.000) < 0.05 coefficients regress 0.938, and R square 0.99. Conclusion: Primigravida and age have a correlation with the incidence of preeclampsia/eclampsia